(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article explores strategies for developing mathematical literacy in primary grades, with a focus on aligning teaching practices and curricula with international standards. It highlights the importance of mathematical literacy for young learners, emphasizing critical thinking, problem- solving, and analytical skills. The paper examines various pedagogical approaches, such as inquiry-based learning, digital tools, and collaborative problem-solving techniques, that contribute to fostering mathematical skills. It also discusses challenges, such as curriculum discrepancies and resource limitations, and offers practical recommendations for educators to enhance the effectiveness of math instruction in primary education.